Effect of home and in-office bleaching systems on the nanomechanical properties of tooth enamel - Abdurhman Abu-saq Al Yami; Saleh Al Qahtani; Nada Shokair; Mohammed Al Ghamdi; Roula Al Bouni (Elsevier, 2020)
Objectives: The purpose of this in vitro laboratory study was to gauge the nanomechanical properties of the tooth enamel surface using home and in-office bleaching products. Methods: Thirty-six extracted lower lateral incisor teeth (sound and without caries, cracks or restorations) were selected. A silicone mould was used to affix the samples in resin after cutting away the roots. Next, the samples were indiscriminately divided into three treatment groups, i.e., 12 teeth in each study group (control, Opalescence Home, and Opalescence Boost), and treated according to their respective group procedures. Surface topography, nano-indentation, and visual analyses were performed. Data were examined statistically using one-way analysis of variance (p < 0.05) Results: Both experimental bleaching products enhanced the surface roughness when compared to the samples in the control group. However, the control and Opalescence Boost groups showed insignificant differences. The lowest mean nanohardness (GPa) was observed in the Opalescence Boost group (1.56 GPa ± 0.68 GPa). In contrast, the highest mean nanohardness (GPa) was perceived in the control group (3.53 GPa ± 1.06 GPa). The modulus of elasticity was highly affected using Opalescence Boost (182.63 GPa ± 109.13 GPa) when compared to Control (322.69 GPa ± 168.24 GPa). On visual examination, pronounced roughness was observed in both the Opalescence Home and Opalescence Boost groups. Conclusion: Both teeth whitening products damaged the enamel surface either by roughening the tooth surface or by affecting the nanomechanical properties. Therefore, teeth whitening products may be used, but with great caution.